Pulmonary Endarterectomy For Large Vessel Pulmonary Arteritis Mimicking Chronic Thromboembolic Disease - Murathan KÜÇÜK; Can Ramazan ÖNCEL; Mustafa UÇAR; Aytül Belgi YILDIRIM; Bedrettin YILDIZELİ (Archives of Rheumatology, 2016)
Takayasu’s arteritis is a chronic, non-specific primary and inflammatory disease of large vessels, especially the aorta and its branches. Although pulmonary artery involvement is common, clinical signs of pulmonary artery involvement as the initial presentation is rare. Considering Takayasu’s arteritis in the early diagnosis is important. In this article, we report a 23-year-old female patient of Takayasu’s arteritis who was treated with successful surgery combined with medical therapy.